Pregnancy risks in women with pre-existing coronary artery disease, or following acute coronary syndrome. Issue 7 (6th January 2015) - Burchill, Luke J; Lameijer, Heleen; Roos-Hesselink, Jolien W; Grewal, Jasmine; Ruys, Titia PE; Kulikowski, Julia D; Burchill, Laura A; Oudijk, M A; Wald, Rachel M; Colman, Jack M; Siu, Samuel C; Pieper, Petronella G; et al.
Abstract : Objective: The objective of this study was to determine outcomes in pregnant women with pre-existing coronary artery disease (CAD) or following an acute coronary syndrome (ACS) including myocardial infarction (MI). Background: The physiological changes of pregnancy can contribute to myocardial ischaemia. The pregnancy risk for women with pre-established CAD or a history of ACS/MI is not well studied. Methods: This was a retrospective multicentre study. Adverse maternal cardiac, obstetric and fetal/neonatal events were examined. The primary outcome was a composite endpoint of cardiac arrest, ACS/MI, ventricular arrhythmia or congestive heart failure. The prevalence of new or progressive angina during pregnancy was also examined. Results: Fifty pregnancies in 43 women (mean age 35±5 years) were included. Coronary atherosclerosis (40%) and coronary thrombus (36%) were the most common underlying diagnoses. The primary outcome occurred in 10% (5/50) of pregnancies and included one maternal death secondary to cardiac arrest. Other events included ACS/MI (3/50) and heart failure (1/50). New or progressive angina occurred in 18% of pregnancies. Ischaemic complications of any type (new or progressive angina, ACS/MI, ventricular arrhythmia, cardiac arrest) occurred more commonly in women with coronary atherosclerosis compared with those without (50% vs 10%, p=0.003). A high rate of adverse obstetric (16%) and fetal/neonatal (30%) events was observed. Conclusions: Pregnant women with pre-existing CAD or ACS/MI before pregnancy are at increased risk of adverse events during pregnancy. Those with coronary atherosclerosis are at highest risk of adverse maternal cardiac events due to myocardial ischaemia during pregnancy.